Determinants of Economic Growth in 8 ASEAN Countries 2008-2022 - Padli Pawaid Yahya; Taosige Wau; Baiq El Badriati (Universitas Airlangga, 2025)
Objective: This research aims to further examine the influence of investment, corruption, inflation, labor, and trade openness, and it can be seen that these are the determinants of economic growth through several of these variables in the ASEAN region countries for the 2008-2022 period. Methods: Panel data regression is analyzed using three approaches: the Common Effect Model (CEM), the Fixed Effect Model (FEM), and the Random Effect Model (REM). Model selection is determined through the Chow, Hausman, and Lagrange Multiplier tests. Classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) and significance tests (F-test, t-test, and R²) are conducted using EViews 10. Findings: Summarize the key results of your analysis. Highlight the main empirical relationships, theoretical outcomes, or trends identified in the study. Focus on the economic significance of these findings, how they contribute to understanding behaviors, mechanisms, or policy effects relevant to the research question. Originality/value: So that statistical results can be found by showing various variants, especially in the variables of corruption and inflation have no effect on economic growth, while the other three variables together, investment, labor and trade openness have a positive and significant effect on economic growth. Practical/Policy implication: Outline the practical implications of your findings for economic policy, regulation, or institutional decision-making. Suggest how policymakers, economists, or public institutions might apply your results. Where applicable, indicate how your research could guide future interventions, policy design, or economic reforms.